Healthy Food For Kids (SAYA SIHAT) Courseware / Nur Hidayah Fatihah Rohan - Rohan, Nur Hidayah Fatihah (2018)
Learning of the healthy food in kindergarten is taught rarely because of lack of material. The current process used in teaching process is using phonic method. One of the possible solutions in teaching the healthy food is by using courseware. Thus Healthy Food for Kids (I am Healthy) were developed. The interactive multimedia courseware can be helped in the process of teaching and learning. Through this method students can enhance their knowledge through the attractive and interesting gamed-based platform in their studies. Through this courseware the student can learn more about the healthy food. This courseware is developed for the kindergarten student in grabbing their attention in learning process about the healthy food. In developed this courseware, the ADDIE model is using as a based. All elements of multimedia are involved in this courseware in order to grab their attention towards subject. So, a survey was conducted for 30 respondents in order to know the interface, navigation, activity, usability, contents and elements of multimedia are satisfied for the target user. The highest mean for all the construct for user evaluation is 4.27 with standard deviation of 0.74.